Tata Kelola Perbankan Syariah - Erni Erni; Najmi Rehani; Ilham Ilham (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The abstract in this document emphasizes that good corporate governance (GCG) is very important in managing Islamic banking to be in line with Islamic principles. This article discusses the implementation of GCG in the context of Indonesian Islamic banking, especially in maintaining a balance between stakeholder interests and Islamic obligations. Emphasis is given to the role of the Sharia Supervisory Board (SSB), the importance of transparency, accountability, and a risk management system that is in accordance with Islamic principles.